Teachers’ acceptance of mobile technology use towards innovative teaching in Malaysian secondary schools - Siti Noor Ismail; Mohd Norakmar Omar; Yahya Don; Yoppy Wahyu Purnomo; Muhamad Dzahir Kasa (International Journal of Evaluation and Research in Education (IJERE), 2022)
The integration of mobile technology is not a new thing nowadays. It became increasingly applied after the COVID-19 pandemic hit the world. Teachers need to use mobile technology devices widely to improve teaching effectiveness. This study aimed to explore the elements of teachers' acceptance of mobile technology as a learning alternative. The respondents consisted of 422 teachers in 24 secondary schools around Kedah, Malaysia. The results showed that teachers are impressed to integrate mobile technology based on three dimensions: effort expectancy, hedonic motivation, and habit. This situation reflects teachers' willingness to translate their pedagogical abilities through the medium of technology. It has also recognized that internal motivation and teachers' natural habits are the driving force behind integrating mobile technology as a teaching aid to digital technology. Thus, mobile technology is a trend of daily use and can be utilized as the most advanced pedagogical material to go through learning in the 21st century.